Tendencje na światowym i polskim rynku ubezpieczeń kredytu - Lisowski, Jacek (Tendencies in the Global and the Polish Credit Insurance Market, 2008)
The Polish credit insurance market is becoming dependent on the trends in the global credit insurance market. The globalization, deregulation, growing foreign investments, boom in the market, falling number of insolvency, improving quality and availability of credit information exert the influence on credit insurance market structure, market behaviour and results of the Polish and the global credit insurers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 213-219